Impact of Kefiran Exopolysaccharide Extraction on Its Applicability for Tissue Engineering and Regenerative Medicine - Susana Correia; Cristiana Gonçalves; Joaquim M. Oliveira; Hajer Radhouani; Rui L. Reis (Pharmaceutics, 2022)
Kefiran is an exopolysaccharide produced by the microflora of kefir grains used to produce the fermented milk beverage kefir. The health-promoting and physicochemical properties of kefiran led to its exploration for a range of applications, mainly in the food industry and biomedical fields. Aiming to explore its potential for tissue engineering and regenerative medicine (TERM) applications, the kefiran biopolymer obtained through three different extraction methodologies was fully characterized and compared. High-quality kefiran polysaccharides were recovered with suitable yield through different extraction protocols. The methods consisted of heating the kefir grains prior to recovering kefiran by centrifugation and differed mainly in the precipitation steps included before lyophilization. Then, kefiran scaffolds were successfully produced from each extract by cryogelation and freeze-drying. In all extracts, it was possible to identify the molecular structure of the kefiran polysaccharide through 1H-NMR and FTIR spectra. The kefiran from extraction 1 showed the highest molecular weight (~3000 kDa) and the best rheological properties, showing a pseudoplastic behavior; its scaffold presented the highest value of porosity (93.2% ± 2), and wall thickness (85.8 µm ± 16.3). All extracts showed thermal stability, good injectability and desirable viscoelastic properties; the developed scaffolds demonstrated mechanical stability, elastic behavior, and pore size comprised between 98–94 µm. Additionally, all kefiran products proved to be non-cytotoxic over L929 cells. The interesting structural, physicochemical, and biological properties showed by the kefiran extracts and cryogels revealed their biomedical potential and suitability for TERM applications.